Dental caries, tobacco usage and associated risk factor of dental caries in patients visiting a government hospital in Western, Nepal - Krishna Subedi; Bhawana Sigdel; Purna Prasad Khanal; Deepa Sharma; Ganesh Chaudhary; Ashish Kunwar Singh; Sunil Paneru (BMC, 2024)
Abstract Background This study was conducted to assess the prevalence of dental caries, tobacco usage, and associated risk factors for dental caries in patients who visited a government hospital in Western, Nepal. Methods This analytical cross-sectional study was conducted from January to April 2022. Patients above 18 years visiting the dental OPD of a government hospital, and who had provided informed consent were enrolled in the study using a convenience sampling technique. As the study also involved an illiterate population, in that case, informed consent was obtained from their respective legal guardian as well. A pretested standardized, close-ended questionnaire was administered by researchers to gather information regarding the associated risk factors and oral hygiene practices. Clinical examination was done for dental caries according to the criteria by the World Health Organization (WHO) using the "DMFT" index (WHO modification 1987). Bivariate and multivariable logistic regression was done and the odds ratio and p-value was calculated. For all tests, statistical significance was set at p < 0.05. Results A total of 219 participants completed the study with a mean age of 31.73 ± 12.46. The prevalence of dental caries and tobacco was found to be 80.36% and 5.02% respectively. Participants without health insurance had 2.35 times higher odds of dental caries (95% CI: 1.03-5.36). Not rinsing the mouth after eating sweets was associated with 3.07 times higher odds of dental caries (95% CI: 1.31-7.18). Those who hadn't visited a dentist in the past 12 months had lower odds (0.42; 95% CI: 0.18-0.94). Eating fresh fruit daily showed statistically higher odds (2.70; 95% CI: 1.04-6.99) of dental caries. Non-tobacco users had higher odds (14.19; 2.55-78.99) of dental caries. Conclusion Dental caries is highly prevalent, while tobacco usage is relatively low. Factors associated with dental caries included lack of health insurance coverage, consumption of fruits once daily, recent dental visits within the past year, not rinsing the mouth with water after consuming sweets, and non-tobacco users.